Proceedings of the Proceedings of the 1st Workshop on Multidisciplinary and Its Applications Part 1, WMA-01 2018, 19-20 January 2019
DOI: 10.4108/eai.20-1-2018.2281888
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Asset Structure and Sales Growth on Capital Structure and its Impact on Corporate Profitability

Abstract: This study aimed to determine the effect of asset structure and sales growth on capital structure and its impact on corporate profitability. The population in this study was food and beverage companies listed on the Indonesia Stock Exchange. Sampling technique used purposive sampling technique, and the number of samples used as many as 9 companies. The method used was multiple linear regression analysis. The results showed that the assets structure affect the capital structure. While sales growth did not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…These results are in line with research conducted [32] which shows the results that asset structure has a negative effect on return on assets. However, the results of this study are not in line with the researcher [20] who showed that the asset structure does not have a negative effect on return on assets. It's not in line with research [16] which shows that asset structure does not have a positive effect on return on assets.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are in line with research conducted [32] which shows the results that asset structure has a negative effect on return on assets. However, the results of this study are not in line with the researcher [20] who showed that the asset structure does not have a negative effect on return on assets. It's not in line with research [16] which shows that asset structure does not have a positive effect on return on assets.…”
Section: Discussioncontrasting
confidence: 99%
“…In measuring the Asset Structure variable, using a proxy that is in accordance with research from [20] using the TANG symbol where the formula is as follows;…”
Section: 𝐷𝑒𝑏𝑑 π‘‘π‘œ πΈπ‘žπ‘’π‘–π‘‘π‘¦ = π‘‡π‘œπ‘‘π‘Žπ‘™ 𝐷𝑒𝑏𝑑 π‘‡π‘œπ‘‘π‘Žπ‘™ πΈπ‘žπ‘’π‘–π‘‘π‘¦mentioning
confidence: 99%